Personalized assessment and management of patients with coexisting supraventricular tachycardia and coronary artery disease: A case series - Bahar, Mokhamad Aswin; Rizal, Ardian (Heart Science Journal, 2026)
Background: Supraventricular tachycardia (SVT) and coronary artery disease (CAD) are common cardiovascular diseases that can exist simultaneously, complicating diagnosis and treatment. This case series aims to present clinical scenarios and management strategies in patients with both conditions, emphasizing the decision-making process between ablation and revascularization. Case Presentations: Three male patients, between 51 and 63 years old, presented with recurrent palpitations which sometimes accompanied by chest discomfort or exertional dyspnea. All patients had cardiovascular risk factors. Angiography revealed either multivessel CAD or a history of percutaneous coronary intervention (PCI). Electrocardiogram (ECG) showed different tachyarrhythmias which included atrioventricular nodal reentrant tachycardia (AVNRT), atrial tachycardia (AT), and Wolff-Parkinson-White (WPW) syndrome. The management strategies depended on the main clinical issue present. The treatment of patients with significant ischemia involved PCI with drug-eluting stents (DES) to achieve both symptom relief and rhythm stabilization. On the contrary, when arrhythmia was the main driver of symptoms, catheter ablation successfully eliminated the tachyarrhythmia and enhanced the quality of life. Conclusions: Adequate diagnosis of arrhythmia, its underlying mechanisms, substrates, and triggers by use of electrophysiological study is crucial for well-adapted, multidisciplinary selection of intervention—catheter ablation, PCI, or both—as key to clinical best results.